Determining the Distribution of Fluorescent Organic Matter in the Indian Ocean Using in situ Fluorometry - Shigemitsu, Masahito; Uchida, Hiroshi; Yokokawa, Taichi; Arulananthan, K.; Murata, Akihiko (Frontiers in Microbiology, 2020)
In order to determine the behavior of marine fluorescent organic matter (FOM) using high-resolution spatial data, in situ fluorometers have been used in the open ocean. In this study, we measured FOM during the Global Ocean Ship-based Hydrographic Investigations Program (GO-SHIP) expedition from early December 2019 to early February 2020, using an in situ fluorometer at 148 stations along the two meridional transects (at ~80°E and ~57°E) in the Indian Ocean, covering latitudinal ranges from ~6°N to ~20°S and ~30°S to ~65°S, respectively. The FOM data obtained from the fluorometer were corrected for known temperature dependence and calibrated using FOM data measured onboard by a benchtop fluorometer. Using the relative water mass proportions estimated from water mass analyses, we determined the intrinsic values of FOM and apparent oxygen utilization (AOU) for each of the 12 water masses observed. We then estimated the basin-scale relationship between the intrinsic FOM and the AOU, as well as the turnover time for FOM in the Indian Ocean (410 ± 19 years) in combination with the microbial respiration rate in the dark ocean (> 200 m). Similar to previous estimates in the global tropical and subtropical ocean, the FOM turnover time obtained is of the same order of magnitude as the circulation age of the Indian Ocean, indicating that the FOM is refractory and is a sink for reduced carbon in the dark ocean. The decoupling of FOM and AOU from the basin-scale relationship was also observed in the abyssal waters of the northern Indian Ocean. The local variability may be explained by the effect of sinking organic matter altered by denitrification through the oxygen-deficient zone on enhanced abyssal FOM production relative to oxygen consumption.